Insulin-degrading enzyme higher in subjects with metabolic syndrome - Sofer, Y.; Nash, Y.; Osher, E.; Fursht, O.; Goldsmith, G.; Nahary, L.; Shaklai, S.; Tordjman, K. M.; Serebro, M.; Touati, E. B.; Yacobi Bach, M.; Marcus, Y.; et al. (Endocrine, 2021)
Metabolic syndrome (MS) is comprised of a cluster of abnormalities in glucose, lipid, and vascular homeostasis, which is most commonly linked to abdominal obesity. MS heralds increased risk for development of diabetes and is linked to impairment in insulin signaling. Insulin-degrading enzyme (IDE) is one of the mechanisms through which insulin blood levels are maintained. It has been previously suggested that controlling IDE levels could provide yet another potential therapeutic approach in diabetes. Here we aim to investigate whether changes in serum IDE levels correlate with the severity of MS. Using a highly sensitive ELISA assay of active IDE in human serum, we found a strong correlation between circulating IDE levels and circulating levels of triglycerides, insulin, and c-peptide and an inverse correlation with HDL cholesterol (HDLc). Serum IDE levels were higher in MS subjects than in control subjects. Hence, circulating IDE may serve as a tool to identify subjects with abnormal insulin metabolism, possibly those with MS that are at risk to develop diabetes.